Authoritative parenting styles as antecedent of entrepreneurial intentions for Vocational High School Students - Maulana Amirul Adha; Ayatulloh Michael Musyaffi; Nova Syafira Ariyanti; Rudy Ansar; Eka Ary Wibawa (The Journal of Community Positive Practices (JCPP), 2023)
This research investigates the effect of authoritative parenting styles to early entrepreneurial competence, and students’ entrepreneurial intention by including self-efficacy and entrepreneurial personality as mediating variables. Vocational high school students in Jakarta province, Indonesia, are the population of this study and the sample size is 347 students. The software package AMOS 25 was employed to conduct structural equation modeling (SEM) for the purpose of data analysis. The results study indicate that the implementation of authoritative parenting styles has a positive effect on the development of early entrepreneurial competence. This, in turn, can foster the students’ entrepreneurial intention. Furthermore, the present research points out the significance of self-efficacy and entrepreneurial personality as mediators. This study makes both theoretical and practical contributions by presenting a tested model that serves as an alternative guide for promoting students' entrepreneurial intentions.